An economic vulnerability index: Its design and use for international development policy - Patrick Guillaumont (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
In response to the need expressed by the UN General Assembly, an economic vulnerability index (EVI) has been defined by the Committee for Development Policy. The present paper, which refers to this index, first examines how a structural economic vulnerability index can be designed for the low-income countries in particular. It recalls the conceptual and empirical grounds of the index, considers the structure of the present EVI, its sensitivity to methodological choices with respect to averaging, as well as related possible improvements, and briefly compares the levels and trends of EVI in various country groups, using a new database from a retrospective EVI. The paper examines how EVI can be used for international development policy, underlining two main purposes: first - the purpose for which EVI was initially designed - is the identification of the least developed countries (LDCs) that are allowed to receive some preferential treatment in aid and trade matters. EVI, in addition to income per capita and human capital, is one of the three complementary criteria a country needs to meet in order to be perceived as a LDC, and consequently it cannot be the sole criterion for countries wishing to avoid exiting the LDC list. And second, EVI is to be used, in addition to other traditional measures, as a criterion for aid allocation between developing countries. We argue that such an inclusion is legitimate for both reasons of effectiveness and equity. The two purposes are presented as complementary.
Keywords: F35; N10; I39; 330; vulnerability; aid allocation; human capital; least development countries